1993
DOI: 10.21273/horttech.3.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination and Postharvest Disease Control

Abstract: A significant portion of harvested produce never reaches the consumer due to, postharvest diseases. Various chemicals have been used to reduce the incidence of postharvest diseases. Many of these materials have been removed from the market in recent years due to economic, environmental, or health concerns. Although somewhat limited in the range of diseases controlled, chlorination is effective when combined with proper postharvest handling practices. Additionally, it is a relatively inexpensive postharvest dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 0 publications
0
29
0
3
Order By: Relevance
“…It becomes un-ionized hypochlorous acid (HOCl) by hydrolysis, which is an extremely potent bactericidal agent (Dukan, Belkin, & Touati, 1999;Huang, Hung, Hsu, Huang, & Hwang, 2008;Okamoto et al, 2006). Hypochlorous acid (HOCl) solution has a characteristic that major chlorine species is hypochlorite ion (OCl À ) when pH is high, while on the other hand, hypochlorous acid produces chlorine gas when pH is low (Boyette, Ritchie, Carballo, Blankenship, & Sanders, 1993). It has also been reported that concentration of un-ionized hypochlorous acid (HOCl) increases when pH range is from 4 to 7 (Nakagawara et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It becomes un-ionized hypochlorous acid (HOCl) by hydrolysis, which is an extremely potent bactericidal agent (Dukan, Belkin, & Touati, 1999;Huang, Hung, Hsu, Huang, & Hwang, 2008;Okamoto et al, 2006). Hypochlorous acid (HOCl) solution has a characteristic that major chlorine species is hypochlorite ion (OCl À ) when pH is high, while on the other hand, hypochlorous acid produces chlorine gas when pH is low (Boyette, Ritchie, Carballo, Blankenship, & Sanders, 1993). It has also been reported that concentration of un-ionized hypochlorous acid (HOCl) increases when pH range is from 4 to 7 (Nakagawara et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although hypochlorites are the most common forms of antimicrobials used in produce wash facilities, their antimicrobial activity is dependent on the concentration of the free available chlorine (HOCl), which in turn is influenced by the pH of the solution (Boyette et al, 1993;White, 1999). Additionally, the overall efficacy of this sanitizer is dependent on the organic matter content, contact time and the initial microbial load (Boyette et al, 1993;White, 1999).…”
Section: [ ( F I G _ 1 ) T D $ F I G ]mentioning
confidence: 99%
“…Additionally, the overall efficacy of this sanitizer is dependent on the organic matter content, contact time and the initial microbial load (Boyette et al, 1993;White, 1999). PAA-based sanitizers have a broad antimicrobial activity, tolerance to a wide range of pH conditions (Artés et al, 2007;Dell'Erba et al, 2007), and do not produce the mutagenic byproducts as with chlorine-based antimicrobials (Kitis, 2004).…”
Section: [ ( F I G _ 1 ) T D $ F I G ]mentioning
confidence: 99%
“…Therefore, for any washing system, it is important to monitor and control the level of disinfectant at all times, to ensure that it is optimal. It is also imperative to maintain chlorine disinfectants within a suitable pH range (Boyette et al . 1993).…”
Section: Fresh Produce Washingmentioning
confidence: 99%